A supramolecular complex based on a Gd-containing polyoxometalate and food-borne peptide for MRI/CT imaging and NIR-triggered photothermal therapy. Issue 23 (21st May 2021) - Zhang, Simin; Li, Meng; Zhang, Yuan; Wang, Ruichun; Song, Yukun; Zhao, Weiping; Lin, Songyi
Abstract : A multifunctional supramolecular complex is reported for the integrated multiple magnetic resonance imaging/computed X-ray tomography (MRI/CT) imaging and photothermal therapy. Abstract : A multifunctional supramolecular complex is reported for the integrated multiple magnetic resonance imaging/computed X-ray tomography (MRI/CT) imaging and photothermal therapy, wherein a gadolinium-substituted paramagnetic polyoxometalate cluster and food-borne antioxidant peptides identified from the trepang protein hydrolysates are introduced. The as-prepared complex maintained an uniform particle size and much better biocompatibility, and is an ideal candidate for the in vivo applications. The complex allows for T1 -weighted MR imaging and a high Hounsfield unit value for enhanced CT imaging. Interestingly, we demonstrate that the complex possesses outstanding photothermal cancer-killing effects due to its high photothermal conversion efficiency under the exposure of an NIR laser and enhanced antibacterial activity to avoid bacterial infection from the thermal therapeutic process. These results indicate that the supramolecular complex platform exhibit potential for accurate medical diagnosis at an early stage and effective eradication of the tumor cells.